Against the wind - Martin, Kat. (Don Mills, Ont. : MIRA, 2011)
When she is forced to return to the home town she hated, widow and single mother Sarah Allen turns to Jackson Raines, with whom she went to high school, for help when her late husband's criminal past comes back to haunt her.
Keywords: Widows -- Fiction; Single mothers -- Fiction; Romantic suspense fiction